Parametric modeling practice for the first-year architecture students learning - Wendy Sunarya; Jackobus Ade Prasetya Seputra; Afif Fajar Zakariya (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
Parametric modelling has been regarded as a prospective skill both in architectural education and practice. It offers capabilities for designers to instantly generate numerous design options and create complex geometries, which can enhance the design creativity. Realizing its potential and capabilities, this study investigates how parametric modelling can be practiced in early architectural education for improving students’ creativity and design skill. The findings of this study are based on the observation of the parametric modelling workshop participated by 150 first-year architecture students in Indonesia. It is concluded that parametric modelling can be feasibly practiced by first-year students as a medium to enhance design creativity. Additionally, parametric modelling can improve students’ design intuition in some respects, that can smooth the design skill development in architectural learning. The lessons for the effective parametric design learning were also discussed in this study, including metaphorical thinking in parametric exploration, active communication between student and lecturer, and emphasis on the inspirational tool.